Modular Negative Pressure Isolation Room for Field Hospital - Pipathattakul, Manop; Borisut, Wiriya (Journal of Advanced Development in Engineering and Science, 2023)
The outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been evaluated as very high risk at the global level by the World Health Organization (WHO). Currently, COVID-19 is labeled as a pandemic. Therefore, efforts have been undertaken to develop equipment to help mitigate the outbreak of COVID-19 rapidly to protect healthcare workers better. In this study, the negative pressure isolation room design with high mobility and the designed ventilation system meets ASHRAE 170:2017 standard. The minimum requirements consist of outdoor air change rate by 2 ACH, total air change rate by 12 ACH, quantity and efficiency of exhaust fan filters, and pressurized at least (-ve) 2.5 Pa. A negative pressure isolation room was designed and fabricated using dimensions as 3 x 3 x 2.4 meters, including an isolation room as 2.3 x 3 x 2.4 meters and an anteroom as 0.7 x 3 x 2.4 meters. Makeup fan and exhaust fan with high-efficiency filter were installed as ventilation system elements. The experiments were conducted by adjusting exhaust fan speed from 30 to 60% with an increment of 10%, and test conditions performed in two cases as without and with two workers to enter and leave from a room. From the experimental results, it is found that exhaust fan speed from 45 to 55% is optimal to make air change rate from 19.71 to 26.04 ACH, makeup fan by the fixed speed can make air change rate about 7.2 ACH, an isolation room is negatively pressurized from (-ve) 6.0 to 16.0 Pa. While two workers open the entrance, an isolation room can maintain the pressure within (-ve) 4.5 – 9.0 Pa. The room pressure can return to equilibrium within 121 to 231s. The smoke test does not detect the leakage and confined space of air in an isolation room. Environmental contamination of SARS-CoV-2 may be a route of viral transmission. However, it can be minimized by a negative pressure isolation room.